The Relationship Between Nutritional Status and Age at Menarche in Adolescent Girls: A Literature Review - Ratnasari, Tri; Soviana, EIida (Manunggal Halim Jaya, 2026)
Menarche or first menstruation is an important indicator in the reproductive development of teenage girls. The age of menarche can be influenced by various factors, one of which is nutritional status. The unbalanced nutritional status, both deficiencies or excesses, can cause menarche to occur earlier or later, which will ultimately have an impact on the physical and psychological health of teenagers. This study aims to determine and conclude the results of various scientific articles regarding the relationship between nutritional status and age of menarche in teenage girls. This study uses a literature review method by analyzing ten articles from the Google Scholar database, which has been accredited by the SINTA (Science and Technology Index) 1-4. The inclusion criteria included articles published in the period 2015-2025, in Indonesian, with the subject being teenage girls who have experienced menarche and are in good health. The results of the analysis showed that the average age of menarche in teenage girls was around 11 - 12 years. Most teenage girls who experienced menarche have good nutritional status (51%). Of the ten articles reviewed, eight showed a significant relationship between nutritional status and age of menarche. Based on the ten articles, it can be concluded that there is a significant relationship between nutritional status and age of menarche in teenage girls. Increased or decreased nutritional status can accelerate or delay the time of menarche. Therefore, monitoring the nutritional status of teenagers is very important to support optimal reproductive health.